Upaya Pencegahan Meningkatnya Pernikahan Dini di Masa Pandemi Covid-19: Studi Pendampingan Pengabdian Masyarakat di Desa Ngetos Kabupaten Nganjuk - A Halil Thahir; Nadlifatul Husna (Abdimas Indonesian Journal, 2021)
This research is entitled "Efforts to Prevent Increased Early Marriage During the Covid-19 Pandemic Ngetos Village, Ngetos District". Researchers are interested in bringing up this theme because of the phenomenon that exists in society regarding early marriage which often occurs among teenagers in the Ngetos Village community, Ngetos District. This research method uses descriptive qualitative method. Data collection is done by interview, observation, and documentation. The purpose of this study is to provide information, understanding to the public regarding the impact of early marriage and provide efforts to prevent early marriage during the COVID-19 pandemic. The negative impact of early marriage is more dominant than the positive impact. Because the risk of early childhood marriage has a negative impact on adolescents and when living a family life. The negative impact of early marriage is that it can have an impact on maternal health, low education of perpetrators of early marriage, experiencing divorce, poverty. Several factors or causes of early childhood marriage include: economy, education. Efforts that can prevent an increase in early childhood marriage during the COVID-19 pandemic are empowering children with information, educating and providing insight to parents to create a good environment, improving the quality of formal education for children, educating children regarding health and reproduction.